Early neurophysiological stimulus processing during a performance-monitoring task differentiates women with bipolar disorder from women with ADHD - Carruthers, Sophie; Michelini, Giorgia; Kitsune, Viryanaga; Hosang, Georgina M.; Brandeis, Daniel; Asherson, Philip; Kuntsi, Jonna (Psychiatry research, 2021)
Adults with attention-deficit/hyperactivity disorder (ADHD) or bipolar disorder (BD) may display similar cognitive impairments and clinical symptoms, which might reflect shared mechanisms. Initial evidence indicates disorder-specific and overlapping neurophysiological alterations using event-related potentials (ERPs) in individuals with BD or ADHD during attentional tasks, but it is unknown whether impairments generalize across other processes and tasks. We conduct the first comparison between women with ADHD (n = 20), women with BD (n = 20) and control women (n = 20) on ERPs from a performance-monitoring flanker task. The BD group showed a significantly attenuated frontal ERP of conflict monitoring (N2) compared to the ADHD group across both low-conflict (congruent) and high-conflict (incongruent) task conditions, and compared to controls in the high-conflict condition. However, when controlling for an earlier attentional ERP (frontal N1), which was significantly reduced in participants with BD compared to participants with ADHD and controls, N2 group differences were no longer significant. These results indicate that ERP differences in conflict monitoring may be attributable to differences in earlier attentional processes. These findings identify neural differences in early attention between BD and ADHD which precede conflict monitoring processes, potentially pointing to distinct neural mechanisms implicated in the two disorders.